Integrating 21st Century Skills in Curriculum and Material Development Course - Pujiati, Hanip (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
The Curriculum and Material Development (CMD) course content is contextualized in accordance with technological advancements in the era of the Fourth Industrial Revolution and the community's need for educators who possess 21st-century skills. This revision involves integrating 21st-century skill values into curriculum development, syllabi, teaching materials, media, methods, and learning evaluation. Therefore, this study focuses on integrating 21st-century skills and 21st-century digital skills, including critical thinking, creative thinking, collaboration, communication, information literacy, media literacy, technology literacy, flexibility, initiative, social skills, productivity, and leadership, into the CMD course. This study employs the Research and Development method, which involves identifying the problem, describing existing issues, creating a design, validating the design with experts, revising the design of the English learning model, conducting trials, and making revisions. The study's outcomes include three areas of integrating 21st-century skills into the CMD course. The first area involves integrating 21st-century skills into the preliminary activity of designing lesson plans. Secondly, in the process, 21st-century skills should be integrated into the design of learning materials and tasks. Finally, after the activity, 21st-century skills should be integrated into the evaluation and reflection process. The CMD course aims to integrate 21st-century skills throughout the language curriculum. It covers Communicative Syllabus Design, Text-Based Syllabus Design, Product-Oriented Syllabus Design, Process-Oriented Syllabus Design, Content-Based Curriculum, Integrated Curriculum, EFL Curriculum, and EFL Syllabuses and Lesson Plans for Indonesian Students.